Planned home compared with planned hospital births: mode of delivery and Perinatal mortality rates, an observational study - Jacoba van der Kooy; Erwin Birnie; Semiha Denktas; Eric A.P Steegers; Gouke J. Bonsel (BMC, 2017)
Abstract Background To compare the mode of delivery between planned home versus planned hospital births and to determine if differences in intervention rates could be interpreted as over- or undertreatment. Methods Intervention and perinatal mortality rates were obtained for 679,952 low-risk women from the Dutch Perinatal Registry (2000-2007). Intervention was defined as operative vaginal delivery and/or caesarean section. Perinatal mortality was defined as the intrapartum and early neonatal mortality rate up to 7 days postpartum. Besides adjustment for maternal and care factors, we included for additional casemix adjustment: presence of congenital abnormality, small for gestational age, preterm birth, or low Apgar score. The techniques used were nested multiple stepwise logistic regression, and stratified analysis for separate risk groups. An intention-to-treat like analysis was performed. Results The intervention rate was lower in planned home compared to planned hospital births (10.9% 95% CI 10.8-11.0 vs. 13.8% 95% CI 13.6-13.9). Intended place of birth had significant impact on the likelihood to intervene after adjustment (planned homebirth (OR 0.77 95% CI. 0.75-0.78)). The mortality rate was lower in planned home births (0.15% vs. 0.18%). After adjustment, the interaction term home- intervention was significant (OR1.51 95% CI 1.25-1.84). In risk groups, a higher perinatal mortality rate was observed in planned home births. Conclusions The potential presence of over- or under treatment as expressed by adjusted perinatal mortality differs per risk group. In planned home births especially multiparous women showed universally lower intervention rates. However, the benefit of substantially fewer interventions in the planned home group seems to be counterbalanced by substantially increased mortality if intervention occurs.